Open Access Publishing Fund Efficiency: An Expansion and Replication of Luo et al. (2022) - Love, Leesa; Seiferle-Valencia, Marco; Kenyon, Jylisa; Kenyon, Jeremy (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2026)
Objective – This study’s objective was to replicate and test Luo et al.’s (2022) proposals regarding open access publishing fund efficiency, specifically the time efficiency of the overall workflow, to better understand the University of Idaho’s Open Access Publishing Fund and provide actionable insights to librarians interested in establishing such a fund at their institutions.Methods – Fund efficiency was evaluated across five fiscal years focusing on the number of days between fund opening, application submission, approval, and expenditure using a Kruskal-Wallis non-parametric test and a Dunn’s test. Variables related to fund efficiency were identified using multiple linear regressions that both replicated and expanded Luo et al.’s (2022) methodology. Lastly, applicants and timing characteristics were summarized using descriptive statistics.Results – None of the observed internal or external factors uniformly affected the fund’s overall time efficiency; rather, these factors targeted specific stages of the application workflow. FY 2021 was the only funding cycle that displayed significant variance for the number of days between fund opening and application submission. Similarly, FY 2024 showed significant variance for the number of days between submission and approval. The number of days between approval and expenditure demonstrated the most fluctuation, with efficiency gradually decreasing between FY 2020 and FY 2022, peaking in FY 2023, and falling again in FY 2024. Fiscal year variations were the only statistically significant factors that had explanatory power for the variation in fund efficiency. Other variables, including the presence of co-authors, applicant rank, applicant discipline, applicant status, payment type, publisher, and award amount did not yield statistically significant p-values for this dataset. However, requiring an article be accepted for publication or already published can greatly improve fund efficiency.Conclusion – In a climate where university budgets are often constrained, fund administrators will need to understand and articulate the efficiency of their fund and find opportunities to decrease the time they and associated fiscal officers spend with each application.